Criminal risks of medical robots turnover - A. A. Shutova (Russian Journal of Economics and Law)
Objective: to identify criminal risks inherent in a medical robot, taking into account its hardware-technological (technological and digital) features, and to construct, based on this analysis, the author’s classification of criminal risks and models of criminal-legal protection of public relations arising in the medical robots’ turnover.Methods: the article uses general scientific (analysis, synthesis, induction, deduction, classification) and specific scientific methods of cognition, and the logical-legal method.Results: The security vulnerability of medical robots causes serious concern in manufacturers, programmers and those interacting with the robots in the healthcare industry. In medical institutions, robots interact closely with children, the elderly and the disabled, and it may not be clear to the patient whether the robot is working properly or being attacked. Any harm caused by a surgical robot as a result of unauthorized access (or other illegal actions) can undermine the public’s faith in medicine and in the healthcare system as a whole. Threats to the safety of medical robots can have further negative consequences for themselves, as such facts of unlawful influence can lead to robots breaking down or harming other nearby equipment that is the property of the healthcare institution, and worse – the life and health of patients or medical workers. In this regard, the paper identifies criminal risks and threats inherent in medical robots, and formulates measures to improve criminal legislation aimed at countering crimes arising against the legal turnover of medical robots (Article 2352 of the Criminal Code of the Russian Federation).Scientific novelty: at the moment there are few Russian studies devoted to the legal regulation and protection of medical robots. Basically, such researches are done by medical scientists. However, in the Russian Federation, there are practically no special theoretical-legal studies, including those devoted to the study of criminal law issues of the protection of these legal relations, which confirms the relevance and significance of our research.Practical significance: the provisions and conclusions of the article can be used to further improve criminal legislation, and also lay the foundation for further research in criminal law science.